A tale of two tails: developing an avian inspired morphing actuator for yaw control and stability. (9th February 2018) - Gamble, Lawren L; Inman, Daniel J
Abstract: Motivated by the lack of research in tailless morphing aircraft in addition to the current inability to measure the resultant aerodynamic forces and moments of bird control maneuvers, this work aims to develop and test a multi-functional morphing control surface based on the horizontal tail of birds for a low-radar-signature unmanned aerial vehicle. Customized macro fiber composite actuators were designed to achieve yaw control across a range of sideslip angles by inducing 3D curvature as a result of bending-twisting coupling, a well-known phenomenon in classical fiber composite theory. This allows for yaw control, pitch control, and limited air break control. The structural response of the customized actuators was determined numerically using both a piezoelectric and an equivalent thermal model in order to optimize the fiber direction to allow for maximized deflection in both the vertical and lateral directions. In total, three control configurations were tested experimentally: symmetric deflection for pitch control, single-sided deflection for yaw control, and antisymmetric deflection for air brake control. A Reynolds-averaged-Navier–Stokes fluid simulation was also developed to compare with the experimental results for the unactuated baseline configuration. The actuator was shown to provide better yaw control than traditional split aileron methods, remain effective in larger sideslip angles, and provide directional yaw stability when unactuated. Furthermore, it was shown to provide adequate pitch control in sideslip in addition to limited air brake capabilities. This design is proposed to provide complete aircraft control in concert with spanwise morphing wings.